Conventional PCR as a reliable method for diagnosing invasive mucormycosis in resource-limited settings. Issue 5 (26th May 2021) - Pandey, Mragnayani; Xess, Immaculata; Singh, Gagandeep; Kumar, Rakesh; Mahapatra, Manoranjan; Jyotsna, Viveka P.; Agarwal, Reshu; Ghosh, Arnab; Iram, Azka; Mani, Prashant
Abstract : Introduction. Invasive mucormycosis (IM) is a life-threatening infection caused by fungi belonging to the order Mucorales. Histopathology, culture and radiology are the mainstay of diagnosis but lack sensitivity, leading to a delay in timely diagnosis and intervention. Recently, PCR-based approaches have been shown to be a promising method in diagnosing IM. Hypothesis/Gap Statement. Molecular-based approaches may be a valuable adjunct to standard conventional methods for diagnosing IM, especially among culture negatives and patients on antifungal therapy. Aim. In the present study we aimed to evaluate the clinical utility of panfungal and Mucorales-specific PCR for diagnosing IM from various clinical specimens. Methodology. This was a prospective study in which 239 clinically suspected cases of IM attending our tertiary care hospital from August 2015 to March 2018 were enrolled. All the cases were defined as 'proven', 'probable' or 'possible' based on EORTC/MSGERC guidelines. In addition to conventional diagnostics (KOH-calcofluor stain and culture), panfungal and Mucorales-specific PCR assays were also performed. The amplified products were sequenced for species identification. In vitro antifungal susceptibility was performed on all the culture-positive isolates. Results. Among 239 clinically suspected cases of IM, only 140 cases were diagnosed by the demonstration of aseptate ribbon-like hyphae on direct microscopy. Culture was positive in 35.7 % (54/140) of direct microscopy-positive samples. Among the proven cases ( n =11), the sensitivity for both Mucorales-specific nested PCR and panfungal PCR was 100 %, but specificity was 91.9 and 73.7% respectively. In probable cases ( n =129), the sensitivity of both the PCRs was 98.5 % and specificity for panfungal PCR was 73.7 and 91.9 % for Mucorales-specific PCR. Conclusion. Pan fungal PCR in combination with Mucorales-specific PCR, followed by sequencing, may play a significant role in IM diagnosis especially among those negative for both direct microscopy and culture.